Yoga Exercise on Reduction of Menstrual Pain among Adolescent Girls - Ilah Maesari; Dayan Hisni; Bunga Tiara Carolin (KHD-Production, 2022)
Abstract Yoga is a relaxation technique, breathing and body positioning to increase strength, balance and reduce pain. This is because when doing exercise the body will produce endorphins. This yoga exercise training is carried out in order to reduce menstrual pain in adolescent girls. According to WHO, the incidence of menstrual pain in the world is very large, on average more than 50% of women in every country had their periods. The prevalence of primary dysmenorrhea in Indonesia is quite high (60-70%) and 15% of them experience severe pain, generally occurring in adolescents and adults. This research service aimed to determine the effectiveness before and after yoga training on menstrual pain in adolescent girls at Husada Winaya Pratama Vocational High School (SMK) Pandeglang.